2015
DOI: 10.1111/bcpt.12373
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Prescribing of Potentially Interacting Drugs during Warfarin Therapy – A Population‐Based Register Study

Abstract: Abstract:We analysed the occurrence of co-prescribing of potentially interacting drugs during warfarin therapy in the community-dwelling population of Finland. We identified drugs having interaction potential with warfarin using the Swedish Finnish INteraction X-referencing drug-drug interaction database (SFINX) and obtained data on drug purchases from the nationwide Prescription Register. We defined warfarin users as persons purchasing warfarin in 2010 (n = 148,536) and followed them from their first prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…Finally, we did not adjust our analyses for concomitant use of CYP3A4 inhibitors or inducers. However, as reported previously, exposure to these medications was rare in our data (<0.5% of individuals in this cohort at warfarin initiation and ≤0.5% of total person‐time exposed to warfarin in 2010 ).…”
Section: Discussionsupporting
confidence: 71%
“…Finally, we did not adjust our analyses for concomitant use of CYP3A4 inhibitors or inducers. However, as reported previously, exposure to these medications was rare in our data (<0.5% of individuals in this cohort at warfarin initiation and ≤0.5% of total person‐time exposed to warfarin in 2010 ).…”
Section: Discussionsupporting
confidence: 71%
“…NSAIDs have been among the most common interacting drugs in inpatients and outpatients taking warfarin [3,4,9,27]. This trend seems to have changed and similar results to ours have been recently published in large register-based studies [11,28,29]. These findings may indicate increased awareness of clinicians of the increased bleeding risk associated with concomitant use of NSAIDs with warfarin.…”
Section: Discussionsupporting
confidence: 82%
“…More importantly, the excess risk caused by drug interactions is predictable and often avoidable by choosing alternative medications. Despite this, previous studies show that up to 60-80% of warfarin users, the majority of whom are older people, are exposed to potential drug interactions [9][10][11][12]. However, to our knowledge, there is no existing research on the frequency of warfarin drug interactions in frail patients compared to non-frail patients.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have shown that polypharmacy in elderly adults is related to adverse drug events and multiple coexisting impairments. 22) We found that polypharmacy was not solely a problem among elderly adults; polypharmacy was also common among younger adults taking warfarin. Warfarin is used for individuals with high-risk conditions such as AF or venous thromboembolism.…”
Section: Discussionmentioning
confidence: 77%